2020
DOI: 10.1371/journal.pone.0241673
|View full text |Cite
|
Sign up to set email alerts
|

Preventative effects of ramelteon against postoperative delirium after elective liver resection

Abstract: Background Postoperative delirium was reported to be associated with increased postoperative mortality after liver resection. Therefore, it is crucial to prevent postoperative delirium in such cases. Ramelteon, an agonist of melatonin receptor has been suggested to be useful for preventing delirium. The aim of this study was to examine whether ramelteon is effective at preventing delirium after elective liver resection. Methods The cases of patients who underwent liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Then, 111 citations were retrieved for the full-text evaluation. The 67 citations were eliminated from this review since twenty-six were not published, [ 40 - 65 ] eleven did not recruit subjects [ 66 - 76 ] three were terminated [ 77 - 79 ], four were withdrawn [ 80 - 83 ] one was suspended [ 84 ] fourteen were recruiting [ 85 - 98 ] two studies were open-label trials, [ 99 , 100 ] four were observational studies, [ 101 - 104 ] one study was a retrospective study [ 105 ], and one study evaluated dexmedetomidine plus melatonin [ 106 ]. As a result, 44 citations of 25 studies were included for qualitative synthesis in this review [ 15 - 20 , 30 , 41 , 107 - 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…Then, 111 citations were retrieved for the full-text evaluation. The 67 citations were eliminated from this review since twenty-six were not published, [ 40 - 65 ] eleven did not recruit subjects [ 66 - 76 ] three were terminated [ 77 - 79 ], four were withdrawn [ 80 - 83 ] one was suspended [ 84 ] fourteen were recruiting [ 85 - 98 ] two studies were open-label trials, [ 99 , 100 ] four were observational studies, [ 101 - 104 ] one study was a retrospective study [ 105 ], and one study evaluated dexmedetomidine plus melatonin [ 106 ]. As a result, 44 citations of 25 studies were included for qualitative synthesis in this review [ 15 - 20 , 30 , 41 , 107 - 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…Risk factors for delirium development were calculated using adjusted odds ratios (aORs) via multivariate logistic regression analysis. Based on previous reports, 39,42 a post-hoc analysis of surgical cases in which ramelteon was used was performed, as the efficacy of ramelteon in preventing delirium may differ depending on the surgical setting and patient characteristics. All statistical analyses were conducted using JMP Pro 16 software (SAS Institute, Cary, NC).…”
Section: Discussionmentioning
confidence: 99%
“…35 Moreover, ramelteon has been reported to be effective in preventing delirium in older adults, 36,37 ICU patients, 38 and patients who have undergone hepatectomy according to a retrospective study. 39 However, meta-analyses have reported that ramelteon exhibits a limited effect on preventing delirium, 40,41 and no consistent findings have been obtained regarding its effectiveness in preventing delirium. There are two interesting reports on the prevention of postoperative delirium with ramelteon.…”
mentioning
confidence: 99%
“…Based on previous data, it was estimated that 400 patients would be required to confirm these effects with an α of 5% and 80% power. Further assuming a 10% loss to follow up, 497 patients were enrolled [Hokuto 2020]. A research nurse entered all baseline and outcome data in the study database.…”
Section: Discussionmentioning
confidence: 99%